Effect of response contingent negative stimulation on selected responses in a moment of stuttering - NS, Viswanath (Journal of All India Institute of Speech and Hearing, 1972)
In recent years one can witness the increasing use of learning constructs and principles in the understanding and treatment of speech disorders. The problem of stuttering comes to the forefront of one’s attention in this respect The first comprehensive book on stuttering with the behavioral-learning Orientation was written by Brutten and Shoemaker (1967). After critically examining the existing theories of stuttering which use learning constructs and principles (Sheehan, 1958; Wischner, 1950; Shames and Sherick, 1963), Brutten and Shoemaker (1967), present the two factor-theory of stuttering. Thus one of the criticisms levelled by them against these theoretical positions is that they cannot explain punishment data related to stuttering satisfactorily. They point out that these theoretical positions generate the prediction that under punishing conditions the frequency of stuttering will decrease in accordance with the law of effect. The data they present leads them to the conclusion that it is possibly true with regard to certain responses in a moment of stuttering (tongue protrusion, foot tapping etc.) and not with others (repetitions and prolongation of sounds and syllables). The latter responses increase in frequency when punished (Martin, et al. 1964).